Anti-diabetic activity of chromium picolinate and biotin in rats with type 2 diabetes induced by high-fat diet and streptozotocin - Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Nurhan; Küçük, Ömersman; Ozercan, Ibrahim H.; Komorowski, James R. (Cambridge Univ Press, 2013)
The objective of the present study was to evaluate anti-diabetic effects of chromium picolinate (CrPic) and biotin supplementations in type 2 diabetic rats. The type 2 diabetic rat model was induced by high-fat diet (HFD) and low-dose streptozotocin. The rats were divided into five groups as follows: (1) non-diabetic rats fed a regular diet; (2) diabetic rats fed a HFD; (3) diabetic rats fed a HFD and supplemented with CrPic (80 mu g/kg body weight (BW) per d); (4) diabetic rats fed a HFD and supplemented with biotin (300 mu g/kg BW per d); (5) diabetic rats fed a HFD and supplemented with both CrPic and biotin. Circulating glucose, cortisol, total cholesterol, TAG, NEFA and malondialdehyde concentrations decreased (P<0.05), but serum insulin concentrations increased (P<0.05) in diabetic rats treated with biotin and CrPic, particularly with a combination of the supplements. Feeding a HFD to diabetic rats decreased PPAR-gamma expression in adipose tissue and phosphorylated insulin receptor substrate 1 (p-IRS-1) expression of liver, kidney and muscle tissues, while the supplements increased (P<0.001) PPAR-gamma and p-IRS-1 expressions in relevant tissues. Expression of NF-kappa B in the liver and kidney was greater in diabetic rats fed a HFD, as compared with rats fed a regular diet (P<0.01). The supplements decreased the expression of NF-kappa B in diabetic rats (P<0.05). Results of the present study revealed that supplementing CrPic and biotin alone or in a combination exerts anti-diabetic activities, probably through modulation of PPAR-gamma, IRS-1 and NF-kappa B proteins.
Keywords: Chromium; Biotin; Glucose; Insulin; PPAR-gamma; Phosphorylated insulin receptor substrate-1; NF-kappa B